CEO narcissism and its influence on innovation capabilities of micro, small, and medium-sized enterprises: An empirical study in the Colombian context - Tobías Alfonso Parodi Camaño; Jhon Víctor Vidal Durango; Ivan Portnoy (PLoS ONE, 2026)
This study explores the relationship between the level of CEO narcissism and the innovation capabilities of firms in Colombia. Two structured instruments were applied to a sample of 85 companies from various economic sectors and organizational sizes. The first instrument measured narcissistic traits in CEOs based on an adaptation of the Narcissistic Personality Inventory (NPI), together with exploratory factor analysis (EFA). The second instrument assessed innovation capabilities across five key dimensions: product/service, internal processes, marketing, knowledge management, and investment in R&D. The results indicate significant associations between specific dimensions of narcissism and particular components of innovation, revealing both potential strengths and risks inherent to such traits. Theoretical and practical implications are discussed concerning the selection and training of executives in highly competitive environments.